Development tools of territories in Russia: an analytical review - A. K. Perevozchikova (Вестник университета, 2023)
The activity of any state is impossible without tools for the development of territories. At the moment, special economic zones, technoparks, scientific and educational centers, etc. operate on the territory of many subjects of the Russian Federation. However, problems related to territorial development remain unresolved. In this article, an analytical review of existing tools for the development of territories (herein-after – IRT) in the Russian Federation is carried out, their significance is shown, the history of their appearance is touched upon. The purpose of the study is to identify problems related to the tools of territorial development in Russia and to develop proposals for their solution. The objectives of this work are next: to conduct a comparative characterization of territorial development tools by 7 indicators, to calculate the percentage of IRT in each macroregion and district, to study foreign experience in implementing tools on the example of the People’s Republic of China, to develop proposals for improving IRT in Russia. The results of the study can be useful for seeing the overall picture of existing tools for the development of territories, for eliminating problems and developing measures to improve the operation of these tools or the emergence of new ones.